ASPREE-D: Aspirin for the prevention of depression in the elderly. (31st May 2016) - Berk, Michael; Woods, R. L.; Nelson, M. R.; Shah, R. C.; Reid, C. M.; Storey, E.; Fitzgerald, S. M.; Lockery, J. E.; Wolfe, R.; Mohebbi, M.; Murray, A. M.; Kirpach, B.; et al.
ABSTRACT: Background: Not only is depression associated with increased inflammation but inflammation is a risk factor for the genesis of depression. Many of the environmental risk factors for depression are transduced through inflammatory signaling. Anti-inflammatory agents show promise for the management of depression in preclinical, epidemiological, and early clinical studies. This opens the door to the potential for anti-inflammatory agents to treat and prevent depression. There are no evidence-based pharmacotherapies for depression prevention. Method: ASPREE-D, aspirin in the prevention of depression in the elderly, is a sub study of ASPREE, which explores the potential of aspirin to prevent a range of inflammation related disorders in the elderly. With a sample size of 19, 114, and a duration of 5 years, this placebo controlled study will be one of the largest randomized controlled trials in psychiatry and will provide definitive evidence on the ability of aspirin to prevent depression. Results: This paper presents the rationale for the study and presents a summary of the study design. Conclusions: ASPREE-D may not only define novel therapy but will provide mechanistic proof of concept of the role of inflammation in depression.